132. Study of the dosimetric robustness of PVA-GTA based Fricke gels against manufacture parameters. (December 2018) - Gallo, S.; Gambarini, G.; Ianni, L.; Veronese, I.
Abstract: Purpose: Fricke gel dosimeters (FGDs) based on poly-vinyl alcohol (PVA) as gelling agent and glutaraldehyde (GTA) as cross-linker, were developed with the aim to overcome the drawbacks affecting the FGDs prepared with traditional natural gel matrices like gelatin or agarose[1] . Here, we investigate the dosimetric robustness of PVA-GTA FGDs against parameters influencing their preparation, like pH and temperature of gelling. Materials and Methods: PVA-GTA matrices undergo gelling by heating instead of cooling. Gelling temperatures from 6 °C to 40 °C were considered. FGDs with PVA and GTA concentrations of 10% w/w and 1% w/w respectively, were arranged preparing Fricke solutions with different amounts of sulfuric acid in the interval 18–100 mM. FGDs in spectrophotometry cuvettes (10 mm optical path) were uniformly irradiated with a 137Cs source. The optical absorbance (OA) properties and dose-response in the interval 0–35 Gy were investigated. Furthermore, FGDs in form of thin layers (3 mm optical path, area 10 × 5 cm 2 ) were irradiated with 80 kV X-rays producing a steep dose gradient. Light transmittance images were acquired before irradiation and at consecutive times up to 6 h post-irradiation to derive the Fe3+ diffusion coefficient. Results: OA spectra and dose-response curves of FGDs were independent of the gelling temperature. A sensitivity of approximately 0.073 Gy-1 was obtained. By contrast, as in traditional FGDs, sulfuric acid concentration significantly affected the OA spectra as well as the sensitivity and linearity of the PVA-GTA FGDs. Both gelling temperature gradient and pH did not influence the Fe3+ diffusion coefficient, assessed equal to approximately 0.22 mm 2 /h, i.e. more than two times lower than in traditional FGDs. Conclusions: The robustness of PVA-GTA-FGDs against preparation parameters represent a significant advantage over traditional FGDs. In particular, the response independence of the gelling temperature may enable the manufacture of large FGD phantoms without any gradient in sensitivity.